Effect of watering schedule on intake and digestibility of nutrients in camels - JAKHMOLA, R C (The Indian Journal of Animal Sciences, 2013)
In Bikaneri camels effect of different watering schedules on intake and digestibility of nutrients were studied. Camels consumed 12.46±0.55, 10.29±0.50 and 6.09±0.71 kg water on a daily basis in daily (DW), twice weekly (BW) ami once weekly (OW) watering schedule, respectively. The dry-matter intake which was highly related to water intake was 5.93±0.155, 4.76±0.450 and 3.83±0.413 kg/day in DW, BW and OWrespeclively. The water intake was closely related to excretion of water in both faeces and urine. The effect on digeslibility of nutrients of watering schedule Was nonsignificant.